Flame-retardant water-resistant magnesium oxysulfate board and manufacturing process thereof

By combining the modified glass fiber cloth with a mixed slurry of sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium sulfhydryl magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnes

CN119797881AActive Publication Date: 2025-04-11JIANGSU JINPENG FIREPROOF BOARD CO LTD

Patent Information

Application Number
CN202411860697.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing magnesium sulfhydryl cement boards have problems of low strength and poor water resistance when used in high humidity environments, which limits their application in swimming pools, bathrooms and other places.

Method used

The magnesium sulfide mixed slurry was prepared by mixing lightly calcined magnesium oxide powder, magnesium sulfate heptahydrate, water, fly ash, citric acid and iminodiacetic acid-type chelating resin, and combined with a modified glass fiber cloth, and a flame-retardant water-resistant magnesium sulfide plate was prepared by hot pressing treatment.

Benefits of technology

It improves the compressive strength, flexural strength and water resistance of magnesium sulfhydryl plates, and at the same time enhances its flame retardant performance, suitable for applications in high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a flame-retardant water-resistant magnesium oxysulfate board and a manufacturing process thereof. The invention discloses the following scheme: mixing light calcined magnesia powder, magnesium sulfate heptahydrate, water, fly ash, citric acid and iminodiacetic acid type chelate resin to obtain magnesium oxysulfate mixed slurry; the preparation method comprises the following steps: by taking hydrogen-terminated polydimethylsiloxane and 10-undecenal as raw materials, reacting, then grafting 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and then carrying out termination by adopting isophorone diisocyanate, so as to obtain an isocyanate-terminated silicon-containing flame retardant; the preparation method comprises the following steps: modifying epoxy resin by using an isocyanate-terminated silicon-containing flame retardant, and mixing with an epoxy flexibilizer and tetraethylenepentamine to prepare an epoxy resin glue solution; and immersing glass fiber cloth into the epoxy resin glue solution, combining with the magnesium oxysulfate mixed slurry, and curing to obtain the magnesium oxysulfate board. The magnesium oxysulfate board prepared by the invention is high in strength and has good flame retardance and water resistance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a flame-retardant and water-resistant magnesium oxysulfide board and a manufacturing process thereof. Background Art

[0002] Magnesium oxysulfate cement is a common inorganic cementitious material for construction, which is formed by mixing and stirring light-burned magnesium oxide powder and magnesium sulfate solution, and then setting and hardening. Since the calcination temperature of magnesium oxide, the main component of magnesium oxysulfate cement, is much lower than the calcination temperature of silicate cement clinker, it has the advantages of low energy consumption, simple production process and low cost. At the same time, magnesium oxysulfate cement also has the advantages of fire resistance, heat resistance, low density, low thermal conductivity and strong bonding force, and is widely used in the production of lightweight wall panels, refractory components, thermal insulation panels, etc.

[0003] However, magnesium oxysulfate cement has defects such as low strength and poor water resistance, and the development of magnesium oxysulfate board made of magnesium oxysulfate cement in the field of building materials has also been restricted, especially in the application of long-term high humidity environments such as swimming pools and bathrooms. Therefore, it is very necessary to invent a new type of magnesium oxysulfate board. Summary of the invention

[0004] The object of the present invention is to provide a flame retardant and water resistant magnesium oxysulfate board and a manufacturing process thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a flame retardant and water resistant magnesium oxysulfide board and a manufacturing process thereof, comprising the following steps: Step 1: Mixing light-burned magnesium oxide powder, magnesium sulfate heptahydrate, water, fly ash, citric acid, and iminodiacetic acid type chelating resin to obtain magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal, stir 10-undecenal and heat it to 45-55° C. under the condition of nitrogen, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as catalyst, stir and heat it to 85-95° C. and keep it for 4-5 hours. After the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 85-100°C and stirring for 15-30 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 12-15 hours, washing and drying to obtain a silicon-containing flame retardant; S3: After drying the silicon-containing flame retardant at 110-120° C. for 2-3 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 50-65° C. for 3-5 hours to obtain an isocyanate-terminated silicon-containing flame retardant; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin; mixing the modified epoxy resin, an epoxy toughening agent, and tetraethylene pentamine to obtain an epoxy resin glue; Step 3: The glass fiber cloth is calcined at 600-900°C for 30-60min, immersed in epoxy resin glue after cooling, taken out and heated to 80-90°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth is laid in a mold, magnesium oxysulfide mixed slurry is poured into it, and then a modified glass fiber cloth is laid on top, and after hot pressing treatment, demolding and curing are performed to obtain a flame-retardant and water-resistant magnesium oxysulfide board.

[0006] Furthermore, in step 1, the contents of the components in the magnesium oxysulfide mixed slurry are, by weight, 25 to 35 parts of light-burned magnesium oxide powder, 30 to 40 parts of magnesium sulfate heptahydrate, 25 to 30 parts of water, 12 to 16 parts of fly ash, 0.15 to 0.25 parts of citric acid, and 1 to 1.5 parts of iminodiacetic acid type chelating resin.

[0007] Furthermore, in S1, hydrogen-terminated polydimethylsiloxane and 10-undecenal are weighed at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:(1.1-1.2).

[0008] Furthermore, in S2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond to aldehyde group of 1:1.

[0009] Furthermore, in S3, the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2.

[0010] Furthermore, in S4, the contents of the components in the modified epoxy resin are, by weight percentage, 10-15% of the isocyanate-terminated silicon-containing flame retardant and 85-90% of the epoxy resin.

[0011] Furthermore, in S4, the modified epoxy resin, epoxy toughening agent, and tetraethylene pentamine are mixed in a weight ratio of 100: (16-18): (20-30).

[0012] Furthermore, in step 3, the hot pressing treatment time is 30-40 min, the temperature is 110-120° C., and the pressure is 2-3 MPa.

[0013] Furthermore, the demoulding and curing conditions are curing at 20-25°C for 20-28 days.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing a flame-retardant and water-resistant magnesium oxysulfide board, wherein light-burned magnesium oxide powder, magnesium sulfate heptahydrate, water, fly ash, citric acid, and iminodiacetic acid type chelating resin are mixed to obtain a magnesium oxysulfide mixed slurry; glass fiber cloth is immersed in epoxy resin glue for modification and then combined with magnesium oxysulfide cement to prepare the magnesium oxysulfide board. The glass fiber cloth has excellent mechanical properties and can provide a certain load-bearing effect, thereby achieving the effect of strengthening the magnesium oxysulfide board.

[0015] The magnesium oxysulfide mixed slurry of the present invention is added with an iminodiacetic acid type chelating resin. On the one hand, the chelating resin has good stability in the slurry, can play a filling role, reduce porosity, and has an optimization effect on the internal structure of the magnesium oxysulfide board; on the other hand, the nitrogen atoms contained in the chelating resin can provide lone pairs of electrons, which are combined with the empty orbits provided by the magnesium ions in the slurry layer to produce a coordination effect; and the carboxyl carboxylic acid in the chelating resin can react with the hydrated hydroxy magnesium ions generated by the hydrolysis of magnesium oxide to induce the growth of slender needle-rod-shaped crystals 5Mg(OH)2·MgSO4·7H2O, and inhibit the generation of flaky Mg(OH)2 phases. The generated 5Mg(OH)2·MgSO4·7H2O interpenetrates with each other to form a dense and firm three-dimensional network structure, fills the gaps and holes in the matrix, and makes the interior of the magnesium oxysulfide board more dense. In addition, the carboxyl group in the chelating resin can also react with the epoxy resin on the surface of the glass fiber cloth to improve the bonding force between the glass fiber cloth and the magnesium oxysulfide cement.

[0016] In order to further improve the modification effect of epoxy resin on glass fiber cloth, the present invention uses hydrogen-terminated polydimethylsiloxane and 10-undecenal as raw materials, prepares terminal aldehyde-modified polysiloxane through a hydrosilylation reaction, and then reacts the product with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain a silicon-containing flame retardant; the silicon-containing flame retardant is reacted with isophorone diisocyanate using the hydroxyl generated by the reaction of the aldehyde group and the PH bond to obtain an isocyanate-terminated silicon-containing flame retardant. The isocyanate-terminated silicon-containing flame retardant contains a flexible silicon-oxygen bond, and adding it to the epoxy resin can not only increase the crosslinking density of the epoxy resin and improve the mechanical properties of the epoxy resin, but also give the epoxy resin good hydrophobicity and flame retardancy, thereby modifying the epoxy resin. During the research and development process, the researchers also found that excessive use of isocyanate-terminated silicon-containing flame retardant will cause it to phase separate from the epoxy resin and affect the modification results. Therefore, when modifying the epoxy resin, 10~15% isocyanate-terminated silicon-containing flame retardant and 85~90% epoxy resin are mixed by weight to achieve the best modification effect. DETAILED DESCRIPTION

[0017] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0018] Materials and sources used in the present invention: lightly burned magnesium oxide powder comes from Haicheng Magnesium Mineral Group Co., Ltd., with the item number CCM-96; hydrogen-terminated polydimethylsiloxane comes from Ningbo Runhe High-tech Materials Technology Co., Ltd., with the item number RH-H518; fly ash comes from Lingshou County Chuangwei Mineral Products Processing, with the item number fmh1100; iminodiacetic acid type chelating resin comes from Tianjin Xinyue Huamei Environmental Protection Technology Co., Ltd., with the item number D401-5; epoxy resin comes from Wanqian Chemical, with the item number WSR618 (E51); epoxy toughening agent comes from Guangzhou Goode New Materials Technology Co., Ltd., model WD-403; glass fiber cloth comes from Changzhou Chengzhida Fiberglass Products Co., Ltd., with the item number 1230.

[0019] Embodiment 1: A flame retardant and water resistant magnesium oxysulfide board and a manufacturing process thereof, comprising the following steps: Step 1: 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, 0.18 kg of citric acid, and 1.2 kg of iminodiacetic acid type chelating resin are mixed to obtain magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:1.2, stir 10-undecenal and heat it to 45°C under nitrogen, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as a catalyst, stir and heat to 85°C for 4h, after the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 85°C and stirring for 15 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 12 hours, washing and drying to obtain a silicon-containing flame retardant; wherein 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond and aldehyde group of 1:1; S3: After drying the silicon-containing flame retardant at 110° C. for 2 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 50° C. for 3 hours to obtain an isocyanate-terminated silicon-containing flame retardant; wherein the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin, wherein the content of each component in the modified epoxy resin is, by weight percentage, 10% of the isocyanate-terminated silicon-containing flame retardant and 90% of the epoxy resin; mixing the modified epoxy resin, the epoxy toughening agent, and tetraethylene pentamine in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 600°C for 30 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 80°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot-pressed for 30 minutes at a hot-pressing temperature of 110°C and a pressure of 2MPa, and cured at 20°C for 20 days after demolding to obtain a flame-retardant and water-resistant magnesium oxysulfide board.

[0020] Embodiment 2: A flame retardant and water resistant magnesium oxysulfide board and a manufacturing process thereof, comprising the following steps: Step 1: 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, 0.18 kg of citric acid, and 1.2 kg of iminodiacetic acid type chelating resin are mixed to obtain magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:1.2, stir 10-undecenal and heat it to 50° C. under nitrogen flow, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as a catalyst, stir and heat it to 90° C. and keep it for 4.5 hours. After the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 90°C and stirring for 25 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 13 hours, washing and drying to obtain a silicon-containing flame retardant; wherein 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond and aldehyde group of 1:1; S3: After drying the silicon-containing flame retardant at 115° C. for 2.5 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 60° C. for 4 hours to obtain an isocyanate-terminated silicon-containing flame retardant; wherein the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin, wherein the content of each component in the modified epoxy resin is, by weight percentage, 13% of the isocyanate-terminated silicon-containing flame retardant and 87% of the epoxy resin; mixing the modified epoxy resin, the epoxy toughening agent, and tetraethylene pentamine in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 750°C for 45 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 85°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot pressed for 35 minutes, the hot pressing temperature was 115°C, the pressure was 2.5MPa, and after demolding, it was cured at 25°C for 24 days to obtain a flame retardant and water-resistant magnesium oxysulfide board.

[0021] Embodiment 3: A flame retardant and water resistant magnesium oxysulfide board and a manufacturing process thereof, comprising the following steps: Step 1: 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, 0.18 kg of citric acid, and 1.2 kg of iminodiacetic acid type chelating resin are mixed to obtain magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:1.2, stir 10-undecenal and heat it to 55°C under nitrogen, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as a catalyst, stir and heat it to 95°C and keep it for 5h, after the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 100°C and stirring for 30 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 15 hours, washing and drying to obtain a silicon-containing flame retardant; wherein 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond to aldehyde group of 1:1; S3: After drying the silicon-containing flame retardant at 120° C. for 3 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 65° C. for 5 hours to obtain an isocyanate-terminated silicon-containing flame retardant; wherein the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin, wherein the content of each component in the modified epoxy resin is, by weight percentage, 15% of the isocyanate-terminated silicon-containing flame retardant and 85% of the epoxy resin; mixing the modified epoxy resin, the epoxy toughening agent, and tetraethylene pentamine in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 900°C for 60 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 90°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot-pressed for 40 minutes at a hot-pressing temperature of 120°C and a pressure of 3MPa, and cured at 25°C for 28 days after demolding to obtain a flame-retardant and water-resistant magnesium oxysulfide board.

[0022] Comparative Example 1: The epoxy resin was not modified, and the other parameters were the same as those in Example 1.

[0023] Step 1: 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, 0.18 kg of citric acid, and 1.2 kg of iminodiacetic acid type chelating resin are mixed to obtain magnesium oxysulfide mixed slurry; Step 2: The epoxy resin, epoxy toughening agent and tetraethylene pentamine are mixed in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 600°C for 30 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 80°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot-pressed for 30 minutes at a hot-pressing temperature of 110°C and a pressure of 2MPa, and cured at 20°C for 20 days after demolding to obtain a flame-retardant and water-resistant magnesium oxysulfide board.

[0024] Comparative Example 2: The magnesium oxysulfide mixed slurry was prepared without adding the iminodiacetic acid type chelating resin, and the other parameters were the same as those in Example 2.

[0025] Step 1: Mix 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, and 0.18 kg of citric acid to obtain a magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:1.2, stir 10-undecenal and heat it to 50° C. under nitrogen flow, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as a catalyst, stir and heat it to 90° C. and keep it for 4.5 hours. After the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 90°C and stirring for 25 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 13 hours, washing and drying to obtain a silicon-containing flame retardant; wherein 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond and aldehyde group of 1:1; S3: After drying the silicon-containing flame retardant at 115° C. for 2.5 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 60° C. for 4 hours to obtain an isocyanate-terminated silicon-containing flame retardant; wherein the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin, wherein the content of each component in the modified epoxy resin is, by weight percentage, 13% of the isocyanate-terminated silicon-containing flame retardant and 87% of the epoxy resin; mixing the modified epoxy resin, the epoxy toughening agent, and tetraethylene pentamine in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 750°C for 45 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 85°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot pressed for 35 minutes, the hot pressing temperature was 115°C, the pressure was 2.5MPa, and after demolding, it was cured at 25°C for 24 days to obtain a flame retardant and water-resistant magnesium oxysulfide board.

[0026] Comparative Example 3: The amount of the isocyanate-terminated silicon-containing flame retardant was increased, and the other parameters were the same as those in Example 3.

[0027] Step 1: 28 kg of light-burned magnesium oxide powder, 36 kg of magnesium sulfate heptahydrate, 27 kg of water, 13 kg of fly ash, 0.18 kg of citric acid, and 1.2 kg of iminodiacetic acid type chelating resin are mixed to obtain magnesium oxysulfide mixed slurry; Step 2: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:1.2, stir 10-undecenal and heat it to 55°C under nitrogen, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as a catalyst, stir and heat it to 95°C and keep it for 5h, after the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 100°C and stirring for 30 minutes, then adding terminal aldehyde-modified polysiloxane under the condition of nitrogen, reacting for 15 hours, washing and drying to obtain a silicon-containing flame retardant; wherein 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react at a molar ratio of phosphorus-hydrogen bond to aldehyde group of 1:1; S3: After drying the silicon-containing flame retardant at 120° C. for 3 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 65° C. for 5 hours to obtain an isocyanate-terminated silicon-containing flame retardant; wherein the silicon-containing flame retardant and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:2; S4: mixing an isocyanate-terminated silicon-containing flame retardant and an epoxy resin to obtain a modified epoxy resin, wherein the content of each component in the modified epoxy resin is, by weight percentage, 30% of the isocyanate-terminated silicon-containing flame retardant and 70% of the epoxy resin; mixing the modified epoxy resin, the epoxy toughening agent, and tetraethylene pentamine in a weight ratio of 100:17:25 to obtain an epoxy resin glue; Step 3: The glass fiber cloth was calcined at 900°C for 60 minutes, immersed in epoxy resin glue after cooling, taken out and heated to 90°C for curing to obtain modified glass fiber cloth; the modified glass fiber cloth was laid in a mold, magnesium oxysulfide mixed slurry was poured into it, and then a modified glass fiber cloth was laid on top, hot-pressed for 40 minutes at a hot-pressing temperature of 120°C and a pressure of 3MPa, and cured at 25°C for 28 days after demolding to obtain a flame-retardant and water-resistant magnesium oxysulfide board.

[0028] Experiment: A magnesium oxysulfide board sample was prepared according to the preparation method in Examples 1 to 3 and Comparative Examples 1 to 3, and the size of the magnesium oxysulfide board sample was 40 mm×40 mm×160 mm; the performance of the magnesium oxysulfide board sample was tested, and the test method was as follows: Flame retardant performance: Tested in accordance with the method in GB / T 5464-2010. Combustion performance classification in accordance with GB 8624-2012.

[0029] Water absorption performance: Place the magnesium oxysulfide board sample at a constant temperature of 40℃ and dry it to constant weight, immerse it in water for 120h, take it out and wipe off the surface moisture and weigh it again, and calculate the water absorption rate according to the formula: Water absorption rate = (M2-M1) / M1×100%; where M2 is the weight of the sample after immersion in water for 24h, and M1 is the weight of the sample when it is dried to constant weight.

[0030] Mechanical properties: Refer to GB / T 17671-2021 to test the compressive strength and flexural strength of magnesium oxysulfide board samples.

[0031]

[0032] Conclusion: The magnesium oxysulfide board prepared by the present invention has good flame retardant and water-resistant properties. The data of Example 1 and Comparative Example 1 show that the magnesium oxysulfide board obtained by impregnating the glass fiber cloth with the modified epoxy resin has higher compressive and flexural strength; the flame retardant and hydrophobic properties of the modified epoxy resin are improved, thus giving the magnesium oxysulfide board good flame retardant and water-resistant properties. The data of Example 2 and Comparative Example 2 show that after adding the iminodiacetic acid chelating resin, the stability in the magnesium oxysulfide mixed slurry is good, which can play a filling role, reduce the porosity, and also improve the bonding force between the glass fiber cloth and the magnesium oxysulfide cement. The data of Example 3 and Comparative Example 3 show that after increasing the amount of isocyanate-terminated silicon-containing flame retardant, the performance of the modified epoxy resin decreases, and the performance of the prepared magnesium oxysulfide board decreases.

[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of a flame retardant and water resistant magnesium oxysulfate board, characterized in that: The following steps are involved: Step 1: Mixing light-burned magnesium oxide powder, magnesium sulfate heptahydrate, water, fly ash, citric acid, and iminodiacetic acid type chelating resin to obtain magnesium oxysulfide mixed slurry; Step 2: Mixing modified epoxy resin, epoxy toughening agent and tetraethylenepentamine to obtain epoxy resin glue; Step 3: The glass fiber cloth is calcined at 600-900°C for 30-60 minutes, immersed in epoxy resin glue after cooling, and then taken out and heated to 80-90°C for curing to obtain a modified glass fiber cloth; The modified glass fiber cloth is laid in the mold, the magnesium oxysulfide mixed slurry is poured in, and then a modified glass fiber cloth is laid on top. After hot pressing treatment, the mold is demoulded and cured to obtain a flame retardant and water-resistant magnesium oxysulfide board.

2. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 1, characterized in that: In step 1, the contents of the components in the magnesium oxysulfide mixed slurry are, by weight, 25 to 35 parts of light-burned magnesium oxide powder, 30 to 40 parts of magnesium sulfate heptahydrate, 25 to 30 parts of water, 12 to 16 parts of fly ash, 0.15 to 0.25 parts of citric acid, and 1 to 1.5 parts of iminodiacetic acid type chelating resin.

3. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 1, characterized in that: In step 2, the modified epoxy resin, epoxy toughening agent, and tetraethylene pentamine are mixed in a weight ratio of 100: (16-18): (20-30).

4. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 1, characterized in that: In step 2, the preparation method of modified epoxy resin, The following steps are involved: S1: Weigh hydrogen-terminated polydimethylsiloxane and 10-undecenal, stir 10-undecenal and heat it to 45-55° C. under the condition of nitrogen, then add hydrogen-terminated polydimethylsiloxane, use chloroplatinic acid isopropanol solution as catalyst, stir and heat it to 85-95° C. and keep it for 4-5 hours. After the reaction is completed, remove excess 10-undecenal by rotary evaporation to obtain terminal aldehyde-modified polysiloxane; S2: adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous toluene, heating to 85-100°C and stirring for 15-30 minutes, adding terminal aldehyde-modified polysiloxane under nitrogen gas flow, reacting for 12-15 hours, washing and drying to obtain a silicon-containing flame retardant; S3: After drying the silicon-containing flame retardant at 110-120° C. for 2-3 hours, isophorone diisocyanate is added to the silicon-containing flame retardant, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 50-65° C. for 3-5 hours to obtain an isocyanate-terminated silicon-containing flame retardant; S4: Mixing the isocyanate-terminated silicon-containing flame retardant and the epoxy resin to obtain a modified epoxy resin.

5. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 4, characterized in that: In S1, hydrogen-terminated polydimethylsiloxane and 10-undecenal are weighed at a molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds of 1:(1.1-1.2).

6. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 4, characterized in that: In S2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and terminal aldehyde-modified polysiloxane react in a molar ratio of phosphorus-hydrogen bond to aldehyde group of 1:

1.

7. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 4, characterized in that: In S3, the silicon-containing flame retardant and isophorone diisocyanate react in a molar ratio of hydroxyl group to isocyanate group of 1:

2.

8. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 4, characterized in that: In S4, the content of each component in the modified epoxy resin, by weight percentage, is 10-15% of the isocyanate-terminated silicon-containing flame retardant and 85-90% of the epoxy resin.

9. The preparation process of a flame retardant and water resistant magnesium oxysulfate board according to claim 1, characterized in that: In step 3, the hot pressing treatment time is 30-40 minutes, the temperature is 110-120°C, and the pressure is 2-3 MPa; the demolding and curing conditions are curing at 20-25°C for 20-28 days.

10. The flame retardant and water resistant magnesium oxysulfide board prepared by the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • METHOD AND DEVICE FOR MANUFACTURING MOLDED PARTS

    AT525545B1

  • Preparation method of reinforced concrete beam with demounting-free textile reinforced concrete (TRC) bottom mould

    CN102814861A

  • Preparation method of nano-reinforcing TRC composite material

    CN107311571A

  • Production process of environment-friendly magnesium oxysulfate material and magnesium oxysulfate board

    CN114634348A

  • Modified epoxy resin and preparation method thereof

    CN115028965A

Cited By

  • High-flame-retardant polyurethane insulation board and preparation method thereof

    CN121406122A

  • High flame-retardant polyurethane insulation board and preparation method thereof

    CN121406122B